A mixed-method process evaluation of an East Midlands county summer 2021 holiday activities and food programme highlighting the views of programme co-ordinators, providers, and parents - Stringer, A.; Bayes, N.; Bradley, S.; Kay, A. D.; Jones, P. G. W.; Ryan, D. J. (Frontiers in Public Health, 2022)
Background: The Holiday Activities and Food (HAF) Programme is a UK Government initiative created to alleviate food insecurity and promote health and wellbeing among children and their families, who are eligible for Free School Meals (FSM) during the school holidays. This process evaluation investigated factors that facilitated and acted as a barrier to the delivery of the HAF Programme from the perspectives of key stakeholders (Co-ordinators, Providers, and Parents) involved in the HAF Programme across an East Midlands county. Methods: This evaluation utilised a mixed methods approach, incorporating focus groups and online surveys to gain rich, multifaceted data. The focus groups were analysed using a hybrid inductive-deductive thematic analysis and the online surveys were analysed using mixed methods approach due to the variation in question type (i.e. quantitative, Likert scale and open response) to align themes to the Government Aims and Standards of the HAF Programme. Findings: The stakeholders highlighted several factors that facilitated and acted as a barrier to the delivery of the HAF Programme. Facilitating factors included existing and maintaining relationships between Co-ordinators, Providers, and facilities/schools/communities as this improved communication and attendance. Additionally, transport provision for those attending the Programme helped overcome barriers to attendance. The primary barrier of the Programme was the late awarding of the Programme contract as this limited the time available to prepare and organise the Programme. This in turn, had several ‘knock on’ effects that created more barriers and resulted in some of the Government Aims and Standards not being met such as, nutrition education for children and parents. Despite the challenges faced, Co-ordinators and Providers were able to deliver the Programme and positively impact upon the children and their families that attended the Programme. Conclusion: Following the facilitators and barriers that were highlighted in this evaluation, several recommendations have been made to enhance the delivery of the HAF Programme and ensure Government Aims and Standards, to improve children and family's health and wellbeing, are attained.